Converting Britannia: Evangelicals and British Public Life, 1770-1840. By Gareth Atkins. Studies in the Eighteenth Century. Woodbridge: Boydell, 2019. xvi + 329 pp. $80.00 cloth. - Larsen, Timothy (Church history, 2020)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0009640720001043/resource/name/firstPage-S0009640720001043a.jpg